Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pada PT Hok Tong Plaju Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2020)
ABSTRACTÂ This study aims to determine the effect of work motivation and work discipline on employee productivity at PT Hok Tong Plaju Palembang. This research method is a quantitative research method, with a population of 328 employees at PT Hok Tong Plaju Palembang. From a population of 382 employees, the Croum Production section was selected as many as 86 employees. Analysis of the data used is simple regression analysis, multiple linear regression analysis, correlation coefficient, coefficient of determination (R2), t test and F test. Based on the results of the study it can be seen that the significant value between work motivation and work discipline partially on employee productivity at PT .Hok Tong Plaju Palembang with a significant value of 0.000